Cognitive Avoidance as a Mediator Between Trauma Exposure and Emotional Numbing - Kalogeropoulos, Dimitra; Papadopoulos, Eleni (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to examine the mediating role of cognitive avoidance in the relationship between trauma exposure and emotional numbing among young adults. Methods and Materials: The research followed a descriptive correlational design using a sample of 445 participants from Greece, selected based on Morgan and Krejcie’s sample size table. Data were collected using three standardized instruments: the Life Events Checklist for DSM-5 (LEC-5) for trauma exposure, the Cognitive Avoidance Questionnaire (CAQ) for cognitive avoidance, and the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) for emotional numbing. Descriptive statistics and Pearson correlation coefficients were computed using SPSS-27. Structural Equation Modeling (SEM) was conducted through AMOS-21 to evaluate the mediating effect of cognitive avoidance and the overall fit of the hypothesized model. Findings: Participants reported moderate levels of trauma exposure (M = 7.83, SD = 2.61), high cognitive avoidance (M = 78.42, SD = 11.97), and moderate emotional numbing (M = 6.14, SD = 1.72). Pearson correlations indicated significant positive associations between trauma exposure and cognitive avoidance (r = .52, p < .001), trauma exposure and emotional numbing (r = .46, p < .001), and cognitive avoidance and emotional numbing (r = .58, p < .001). The SEM analysis confirmed that cognitive avoidance partially mediated the relationship between trauma exposure and emotional numbing. The model demonstrated good fit indices (χ²/df = 2.07, CFI = 0.96, RMSEA = 0.049). Direct, indirect, and total effects were all statistically significant (p < .01), supporting the hypothesized mediation. Conclusion: These findings highlight the importance of addressing cognitive avoidance in therapeutic interventions aimed at reducing emotional disengagement in trauma-exposed individuals, particularly in emerging adult populations.